PEMBUATAN UREA PELEPASAN TERKENDALI MELALUI PELAPISAN DENGAN AMILUM MENGGUNAKAN TEKNOLOGI FLUIDIZED BED SPRAY - Khair Ivanky; Rizki Tri Wahyudi; S Suherman (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Indonesia is one of the largest consumer of nitrogen fertilizer. However, the use of fertilizers has been inefficient because 20-70% content of nitrogenin fertilizers quickly dissolvein water. Therefore, the necessary coating urea with polymer to improve the efficiency of fertilizer nitrogen absorbed so much more. One way to improve the efficiency of urea fertilizer is urea coated with the coating material known as Slow Release Fertilizer (SRF) which is a nitrogen-controlled components. Coating of urea has been widely studied by many researchers, such as urea to the polymer coating is carried out by Liu(2008). The polymers used inthis study is Poly vinyl Alcohol and starch which serves as an adhesive in a coating solution. The range of temperatures used ranged from 350C-500C, the concentration of starch are used10% -50% by weight of coating, and PEG as additives. The tools used are fludized bed as a medium spray to coat and dry urea. The results showed that the higher the operating temperature of the coating efficiency decreases, the dissolution rate decreases and the decrease dustiness. The higher the concentration of coating then the coating efficiency is increased, decreased dissolution rate and increasing dustiness. Microscopy analysis of morphology structure as coated urea particle by using Scanning Electron Microscopy (SEM) show there is obtained two layers.